What affects the intention to invest in equity crowdfunding in Malaysia? / Siew Chein Teo, Tze Wei Liew and Le Wei Yeow - Chein Teo, Siew; Wei Liew, Tze; Wei Yeow, Le (2023)
Crowdfunding is a trending innovative strategy that startups, entrepreneurs, and small businesses employ to secure funds. In this study, we adopt the Transfer Trust Theory as a primary framework to examine how trust in the fundraiser and crowdfunding platform, familiarity, information quality, and innovativeness influence the intention to invest in equity crowdfunding in Malaysia. Data was collected from investors with equity crowdfunding experience (n=200) via a self-administered online questionnaire. This study uses Smart-PLS 4 to validate measurement and structural models. The results demonstrate that information quality, innovativeness, trust in fundraisers, and trust in the platform positively influence investors' intention to invest in equity crowdfunding. Familiarity appears to be the only insignificant factor. Notably, innovativeness emerges as the most dominant factor shaping investment intentions in equity crowdfunding. This research contributes to the existing body of knowledge on crowdfunding and provides valuable insights into the dynamics of equity crowdfunding in Malaysia. Our findings may not be transferable to other cultural or national contexts because our research was limited to the experiences of Malaysian respondents. Implications derived from this research inform equity crowdfunding platform service providers and fundraisers to enhance investment opportunities. Fundraisers can better engage potential investors and boost campaign success by enhancing information quality, innovativeness, and trust-building. This study explores potential factors that have yet to be scrutinized, such as platform and fundraiser trusts, familiarity, information quality, and innovativeness, thereby contributing insights into the effects of these aspects on the investors' intention to invest in equity crowdfunding in Malaysia.